2009
DOI: 10.1186/cc8017
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal life support in severe drug intoxication: a retrospective cohort study of seventeen cases

Abstract: Introduction Cardiovascular failure is the leading cause of death in severe acute drug intoxication. In this setting, we report the feasibility, complications, and outcome of emergency extracorporeal life support (ECLS) in refractory shock or cardiac arrest following a drug overdose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
103
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 34 publications
1
103
0
1
Order By: Relevance
“…Metformin toxicity treated with ECMO has not been previously described. Nonpharmaceutical exposures involving ECMO as a treatment modality have been reported sparingly and include carbon monoxide, zinc chloride, arsenic, hydrocarbon pneumonitis, and taxus poisoning [28][29][30][31][32][33][34][35]. Several of the patients in our cohort were due to non-pharmaceutical exposures (bitter almonds/cyanide, carbon monoxide/smoke inhalation, and methanol).…”
Section: Discussionmentioning
confidence: 94%
“…Metformin toxicity treated with ECMO has not been previously described. Nonpharmaceutical exposures involving ECMO as a treatment modality have been reported sparingly and include carbon monoxide, zinc chloride, arsenic, hydrocarbon pneumonitis, and taxus poisoning [28][29][30][31][32][33][34][35]. Several of the patients in our cohort were due to non-pharmaceutical exposures (bitter almonds/cyanide, carbon monoxide/smoke inhalation, and methanol).…”
Section: Discussionmentioning
confidence: 94%
“…ECLS is an effective rescue therapeutic option in refractory cardiogenic shock or cardiac arrest due to drug intoxication as previous articles reported an overall survival with good neurological recovery after ECLS support between 66% and 85% (2,(5)(6)(7)(8)19). Moreover, Masson et al found a statistically significant survival benefit in ECLS-treated cardiotoxic drugs poisonings as compared to the conventional treatment (7).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the scientific literature shows a paucity of data about the use of ECLS in cardiotoxic drugs poisoning and, to the best of our knowledge, the majority of the published studies on this topic are case reports (2) or case series with a small number of patients (5)(6)(7)(8). So, the aim of this report is to present the results of ECLS in the setting of drug intoxication in a single-center experience.…”
Section: Introductionmentioning
confidence: 99%
“…Therapy with ECMO was successfully applied for recovery, before heart transplantation or by default in patient in accidental hypothermia [19]. Promising results were also described in ECMO treated patients with cardiac failure after medicinal poisoning [14]. Aubron et al [20] point out that bleeding and coagulopathy are the most common complications in ECMO-treated patients, apart from neurological, vascular and infectious complications.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there is a tendency to use VA ECMO as a treatment of choice for hypotermic patients [9][10][11][12][13]. Extracorporeal life support may be an effective treatment in patients developing cardiogenic shock due to drug poisoning, not responding to conventional therapy [14].…”
Section: Introductionmentioning
confidence: 99%